Factors Influencing Life Expectancy: Global Evidence from 125 Countries (International Journal of Built Environment and Sustainability, 2025)
The global average lifespan is influenced by a multitude of factors; however, due to limitations in data availability and quality, comprehensive research on their collective impact remains inadequate. Moreover, there is a dearth of studies that concurrently examine the effects of socioeconomic and environmental factors on life expectancy. In certain instances, these factors exhibit conflicting effects, thereby restricting the generalizability of findings across different countries. This paper investigates the associations between various determinants and life expectancy at birth, utilizing 2015 data from 125 nations sourced from the World Health Organization (WHO), the World Bank, and the United Nations (UN). Specifically, it examines the effects of carbon dioxide (CO2) emissions, air pollution (PM 2.5), per capita alcohol consumption, happiness levels, gross domestic product (GDP), obesity rates measured via Body Mass Index (BMI), corruption levels via corruption perception index, and government health expenditures on life expectancy. Through regression analysis, significant associations are identified between alcohol consumption, happiness levels, CO2 emissions, and air pollution and life expectancy, illustrating the complex interplay of socioeconomic, environmental, and individual lifestyle elements in determining longevity.
Keywords: Life expectancy, associations, multiple linear regression, socioeconomic factors, environmental factors